Multi-Photon Nanosurgery in Live Brain - Allegra Mascaro, Anna Letizia; Sacconi, Leonardo; Pavone, Francesco S. (Frontiers in Neuroenergetics, 2010)
In the last few years two-photon microscopy has been used to perform in vivo high spatial resolution imaging of neurons, glial cells and vascular structures in the intact neocortex. Recently, in parallel to its applications in imaging, multi-photon absorption has been used as a tool for the selective disruption of neural processes and blood vessels in living animals. In this review we present some basic features of multi-photon nanosurgery and we illustrate the advantages offered by this novel methodology in neuroscience research. We show how the spatial localization of multiphoton excitation can be exploited to perform selective lesions on cortical neurons in living mice expressing fluorescent proteins. This methodology is applied to disrupt a single neuron without causing any visible collateral damage to the surrounding structures. The spatial precision of this method allows to dissect single processes as well as individual dendritic spines, preserving the structural integrity of the main neuronal arbor. The same approach can be used to breach the blood-brain barrier through a targeted photo-disruption of blood vessels walls. We show how the vascular system can be perturbed through laser ablation leading towards two different models of stroke: intravascular clot and extravasation. Following the temporal evolution of the injured system (either a neuron or a blood vessel) through time lapse in vivo imaging, the physiological response of the target structure and the rearrangement of the surrounding area can be characterized. Multi-photon nanosurgery in live brain represents a useful tool to produce different models of neurodegenerative disease.